Knowledge regarding Human Papilloma Virus (HPV) infection and vaccine among health science undergraduate students in public University Malaysia - Yew Roan Nee, Santhi; Rosdi, Noor Najiha; Abdul Halain, Azura; Japar, Salimah; Soh, Kim Geok; Ong, Swee Leong; Soh, Kim Lam (Wolters Kluwer - Medknow Publications and Media, 2021)
Human Papillomavirus (HPV), a sexually transmitted virus, is linked to genital warts and cervical cancer. Despite of the availability of HPV vaccination as the primary preventive method against HPV infection, the level of knowledge and understanding about HPV infection and vaccine varied. The aim of this study was to determine the level of knowledge and attitudes towards HPV infection and vaccine among health sciences undergraduate’s students inpublic university Malaysia. This was a cross-sectional study and 251 students were recruited using stratified random sampling methods. The results show that only 42.6% of the respondents had good knowledge regarding HPV infection and vaccination. Conclusion: More than half of the respondents still have poor level of knowledge regarding HPV infection and vaccine Hence, these findings indicate that there is a need for more health education and promotion programme regarding HPV infection and its vaccine among the population studied to further enhance their knowledge and attitude.